Role of Chief Integrity Officer in Malaysian Public Sector - Asmawati, Sajari; Hasnah, Haron; Ishak, Ismail (Universiti Malaysia Pahang, 2016)
This descriptive paper provides an overview of the initiatives taken by the Malaysian government in introducing the role of Chief Integrity Officer to overcome the major challenges of achieving Vision 2020 i.e. Government Transformation Program – fighting corruption. Chief Integrity Officer is perceived to have direct relationship with the level of ethics and integrity in Malaysian public sector organization which consequently will increase the perception of public trust. Nevertheless, there is no such study has been conducted on the impact of Chief Integrity Officer in Malaysian public sector. Thus, this paper gives some insight and summary of the implementation of Chief Integrity Officer as the unit of analysis for future studies and the development of CISM as the measurement tool for analyzing the level of ethics and integrity in public sector.